Analysis of autonomous navigation methods for drone swarms: centralized and decentralized approaches - Sukhomlinova, D. A.; Sotnik, S. V. (ХНУРЕ, 2026)
The work is dedicated to a comprehensive comparative analysis of autonomous navigation methods for swarms of unmanned aerial vehicles. It examines the conceptual differences, technical advantages, and critical disadvantages of centralized and decentralized control approaches in complex environments. Based on aggregated data, key algorithmic foundations (Swarm Intelligence, APF), issues of scalability, fault tolerance, the impact of communication interference, and cybersecurity threats are analyzed. Prospects for the use of adaptive hybrid architectures and Edge Computing to enhance the overall efficiency and autonomy of the swarm are presented. The results of the analysis can be used for the informed selection of swarm control architecture when designing systems for civilian and military applications.
Аналіз методів автономної навігації для рою дронів: централізований та децентралізований підходи
Робота присвячена комплексному порівняльному аналізу методів автономної навігації для роїв безпілотних літальних апаратів. Розглядаються концептуальні відмінності, технічні переваги та критичні недоліки централізованих і децентралізованих підходів до управління в складних умовах. На основі об’єднаних даних проаналізовано ключові алгоритмічні бази (Swarm Intelligence, APF), питання масштабованості, стійкості до відмов, вплив завад зв’язку та загрози кібербезпеки. Наведено перспективи використання адаптивних гібридних архітектур та Edge Computing для підвищення загальної ефективності та автономності рою. Результати аналізу можуть бути використані для обґрунтованого вибору архітектури управління роєм при проєктуванні систем для цивільних та військових застосувань.
Keywords: autonomous navigation; кіберстійкість; Edge Computing; centralized control; штучні потенційні поля; decentralized control; swarm intelligence; ройовий інтелект; децентралізоване управління; централізоване управління; artificial potential fields